Synaptic Plasticity - Heinbockel, Thomas (IntechOpen, 2017)
Nerve cells form thousands of contact points, the synapses, to communicate information with other neurons and target cells. Synapses are sites for changes in brain function through modification of synaptic transmission termed synaptic plasticity. The study of synaptic plasticity has flourished over the years with the advancement of technical breakthroughs and is a timely scientific endeavor today just like it was several decades ago. This book contributes to our understanding of synaptic plasticity at the molecular, biochemical, and cellular systems and behavioral level and informs the reader about its clinical relevance. The book contains ten chapters in three sections: (1) "Mechanisms of Synaptic Plasticity," (2) "Neural Plasticity," and (3) "Plasticity and Neurological Diseases." The book provides detailed and current reviews in these different areas written by experts in their respective fields. The mechanisms of synaptic plasticity and its relation to neurological diseases are featured prominently as a recurring theme throughout most chapters. This book will be most useful for neuroscientists and other scientists alike and will contribute to the training of current and future students who find the plastic nervous system as fascinating as many generations before them.